001 DECIDE: User Involvement in Guideline Development. (15th August 2013) - Callaghan, M; Harbour, R
Abstract : The European Union funded project, DECIDE aims to improve the dissemination of evidence based recommendations by building on the work of GRADE. Work Package 3 aims to identify approaches to effective dissemination and use of research evidence by the general public, in order to improve shared healthcare decision making and person-centred care. This part of the study explores public understanding of clinical guidelines and preferences over future presentation. Focus groups were carried out, to discuss specific guidelines (depression, diabetes, flu vaccination and cervical cancer), and with professionals working in science communication and young people. Questions were informed by a systematic literature review. Data were analysed using the Framework method. Those with experience of a specific illness were better informed and more likely to have actively sought out information than those targeted for screening. Themes emerged including: participants not understanding the concept of 'strong' and 'weak' evidence; participants feeling information should be presented more clearly with emphasis on self-management and side effects; concern expressed that treatment decisions were based on cost rather than evidence; and participants wanted more general information on the condition. Aspects of the content and presentation of guidelines are not relevant or understood by the public. Several different versions of these guidelines have been created based on these results and user testing is ongoing. Current clinical guidelines will need to be adapted substantially before they are appropriate for the public, and the public should be involved in guideline development on an ongoing basis.